Design Proposed for Raw Material Storage Using Assignment Problem Linear Programming in PT Kimia Farma Bandung - Ratman Triwibowo, Ilham
PT Kimia Farma is a company that is active in pharmaceutical industry. There is an increased in demand for drugs production from year to year. Since there is an increased in the production process, therefore the capacity needed of the warehouse for raw material is also increasing and the current warehouse capacity is not enough. Based on the analysis, root cause of this problem is that the arrangement of raw material storage is currently not well-organized. The Warehouse Manager had a plan to change the method that is used to store the raw materials from block stacking method to racking method. If the racking method already applied but the capacity is still not enough, the Warehouse Manager will build an additional warehouse. Therefore, this research aims to propose the dimension of the rack and how to arrange them in the current warehouse, calculate the capacity of the current warehouse if racking method is applied as a reference in determining the additional warehouse capacity, and propose a method to allocate each raw material. In this research, we proposed to use racks with the dimension of each rack is 1,2 x 1,2 x 1,2 m and arrange them vertically so that the capacity of the current warehouse will be up to 166 palettes. We also proposed to change the storage policy from random storage policy to a policy that is considering the in-out frequency of the raw materials (shared storage policy). The model that is used in this research to determine the location of each raw material is assignment problem model using linear programming with minimizing the distance of material handling movement as the objective function. This model has been tested using historical data from July 24th 2018 and has worked aligned with the desired objective function. The result of raw material assignment for the historical data using this model have a distance of material handling movement as much as 99.528,1 meter.